If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(-4) + -3y = -10 Multiply 4 * -4 -16 + -3y = -10 Solving -16 + -3y = -10 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + -3y = -10 + 16 Combine like terms: -16 + 16 = 0 0 + -3y = -10 + 16 -3y = -10 + 16 Combine like terms: -10 + 16 = 6 -3y = 6 Divide each side by '-3'. y = -2 Simplifying y = -2
| 6-6Z=-2(X+5) | | (79x-61y)(49x+5y)= | | 7a/10-3a/10 | | f(0)=1.25x | | 36/11=7/n | | 5(r+9)-5=p | | 0.3(d-100000)=202500 | | 2t+9=36 | | -4x+2x=8 | | 22=-4n+10 | | M-7=2-9 | | 500+115x= | | -7/2=-3/5y-7/3 | | -2=5+n/6 | | 9/2t=-1/9 | | 0.3(d-100000)=1000000 | | 3.5/0.2=n/1.3 | | 7p^2=-28p | | 20-10x-x^2=0 | | 6/25=d-30 | | 8-.8=f-14-2f | | 10=1/4x | | Y/67=-81-(-1262) | | (Y-4)(y^2-5y-2)= | | 10-8x=2(5+4x) | | 36-3r=18-6r | | f(2)=1.25x | | F=-3+2.5x+-1x^2 | | 11w=6w+25 | | -(y-10.9)=1.4y-1.1 | | 5(-X-7)+3=-13 | | -7n(5n-8)=0 |